2005
DOI: 10.1124/mol.105.013615
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of the Anticancer Drug Yondelis (ET-743) on Cell-Cycle Promoters

Abstract: Yondelis is a potent DNA-binding anticancer drug isolated from the tunicate Ecteinascidia turbinata currently undergoing phase III clinical trials. We and others have shown selective inhibition to the transcriptional induction of several genes. We tested the hypothesis that Yondelis specifically targets cell-cycle genes. Our analysis on endogenous and transfected reporter systems revealed complex patterns of transcriptional inhibition and, surprisingly, activation. Other inducible systems-the metallothionein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Other promoters were not significantly affected. These data corroborate the idea that ET-743 is not a general inhibitor of transcription, but that it acts preferentially on some promoters by inhibiting or inducing their activity [31]. The conclusion is also supported by gene Although we have no formal demonstration that the antitumor activity of ET 743 is related to its effects on transcriptional regulation, we can exclude that it acts by inhibiting DNA synthesis.…”
Section: Marine Compounds As Modulators Of Gene Transcriptionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other promoters were not significantly affected. These data corroborate the idea that ET-743 is not a general inhibitor of transcription, but that it acts preferentially on some promoters by inhibiting or inducing their activity [31]. The conclusion is also supported by gene Although we have no formal demonstration that the antitumor activity of ET 743 is related to its effects on transcriptional regulation, we can exclude that it acts by inhibiting DNA synthesis.…”
Section: Marine Compounds As Modulators Of Gene Transcriptionsupporting
confidence: 76%
“…However some genes that were affected, like c-fos, did not contain CCAAT-boxes, indicating that the effects of ET-743 were not specific for NF-Y but that other transcription factors were inhibited. Further studies were performed to investigate the effect of ET-743 on the promoters of genes (cyclin E, E2F1, TK, DHFR, cyclin A, cdc2 and cyclin B2) that regulate the cell cycle by using NIH-3T3 fibroblasts stably transfected with reporter vectors, containing either the CAT or luciferase genes, together with the thyromycin resistance containing vector [31]. Cells synchronized in G0 were stimulated to grow by serum addition, and at several time points the transcriptional activity of these promoters were studied in untreated and ET-743 treated cells.…”
Section: Marine Compounds As Modulators Of Gene Transcriptionmentioning
confidence: 99%
“…Afterward, MPF is reactivated rapidly to enter meiosis II and is maintained at high level during the MII arrest [15]. In culture cells, the chromatin around the genomic region of Cdc2a is acetylated in the histone H4 [16]. Conversely, histone acetylation of H4K12 is altered in oocytes when the kinase activity and synthesis of the CDC2A protein are inhibited [11].…”
Section: Introductionmentioning
confidence: 94%
“…20), and studies also indicated that the drug is not active on all activated genes (e.g., methallothionein, CYP3A4; ref. 21). In addition, trabectedin can inhibit (e.g., DHFR, TK, or cyclin B2) or stimulate (e.g., cyclin E) the activated transcription process.…”
Section: Transcription Regulationmentioning
confidence: 99%